Probiotic metabolites as epigenetic targets in the prevention of colon cancer. (9th November 2012) - Kumar, Manoj; Nagpal, Ravinder; Verma, Vinod; Kumar, Ashok; Kaur, Navrinder; Hemalatha, Rajkumar; Gautam, Sanjeev K.; Singh, Birbal
<x xml:space="preserve">Abstract</x> Dietary interventions for preventing colon cancer have recently attracted increased attention from researchers and clinicians. The probiotics have emerged as potential therapeutic agents but are also regarded as healthy dietary supplements for nutrition and health applications. The probiotic metabolome may interfere with various cellular and molecular processes, including the onset and progression of colon cancer. Probiotic metabolites may lead to the modulation of diverse cellular signal transduction and metabolic pathways. The gut microbial metabolites (organic acids, bacteriocins, peptides, etc.) have been noted to interact with multiple key targets in various metabolic pathways that regulate cellular proliferation, differentiation, apoptosis, inflammation, angiogenesis, and metastasis. Progress in this field suggests that epigenetic alterations will be widely used in the near future to manage colon cancer. The present review provides insights into the molecular basis of the therapeutic applications and the chemopreventive activities of certain probiotic metabolites, with emphasis on the interaction between these metabolites and the molecular signaling cascades that are considered to be epigenetic targets in preventing colon cancer.